Luís de Camões the poet as scriptural exegete - Fleming, John V. 1936- (Boydell & Brewer, 2017)
Second in its fame only to the Lusiads within Camões's large body of poetry, "Sôbolos rios" ("Babylon and Zion") in redondilhas is a philosophically ambitious masterwork of Christian humanism that draws from the psalm Super flumina Babylonis both a general theory of poetry and an intensely focused meditation upon the shape of an individual poet's career. Bringing to bear upon the poem the several learned traditions the poet demands, Fleming's study relates the poem to the traditions of allegorical scriptural exegesis characteristic of the Middle Ages and Renaissance. Specific subjects include the centrality of the psalms and the image of David to European poets, the relation of pagan myth to biblical truth, the complexity and purposefulness of Camoes's intertextual strategies, the underappreciated influence on Camões of Juan Boscán, the exegetical control of the poem's elaborate numerological schemes, and the concept of palinode as literary genre and personal moral statement.John V. Fleming is the Louis W. Fairchild Professor of English and Professor of Comparative Literature emeritus at Princeton University
Title from publisher's bibliographic system (viewed on 29 Sep 2017)
Keywords: Camões, Luís de / 1524?-1580 / Sôbolos rios; Camões, Luís de / 1524?-1580 / Religion; Camões, Luiz de -- 1524-1580; Bible / Psalms, CXXXVII / Criticism, interpretation, etc; Christianity in literature; Religion -- Motiv